The Agile Co-production and Evaluation framework for developing public health interventions, messaging and guidance - Yardley, Lucy; Denford, Sarah; Kamal, Atiya; May, Tom; Kesten, Jo M.; French, Clare E; Weston, Dale; Rubin, G. James; Horwood, Jeremy; Hickman, Matthew; Amlôt, Richard; Oliver, Isabel (Frontiers in Public Health, 2023)
A lesson identified from the COVID-19 pandemic is that we need to extend existing best practice for intervention development. In particular, we need to integrate (a) state-of-the-art methods of rapidly coproducing public health interventions and messaging to support all population groups to protect themselves and their communities with (b) methods of rapidly evaluating co-produced interventions to determine which are acceptable and effective. This paper describes the Agile Co-production and Evaluation (ACE) framework, which is intended to provide a focus for investigating new ways of rapidly developing effective interventions and messaging by combining co-production methods with large-scale testing and/or real-world evaluation. We briefly review some of the participatory, qualitative and quantitative methods that could potentially be combined and propose a research agenda to further develop, refine and validate packages of methods in a variety of public health contexts to determine which combinations are feasible, cost-effective and achieve the goal of improving health and reducing health inequalities.